PENGUATAN KEPEDULIAN LINGKUNGAN MASYARAKAT MELALUI KEGIATAN BERSIH PANTAI DI KAKI BUKIT PECARON, SITUBONDO - Setyono, Bagus Dwi Hari; Jurnal Wicara; Deona, Erenbertha Ni Nyoman Brati; Mardian, Ainnun (Universitas Mataram, 2025)
Coastal areas have an important role in supporting the economic, ecological, and social life of the community. However, the problem of waste, especially plastic, is a serious threat that can reduce environmental quality and hinder the development of the marine tourism potential. This article aims to describe the implementation of the program to strengthen environmental awareness through beach cleaning activities carried out by MBKM KKN students of the University of Mataram in the Kaki Bukit Pecaron area, Klatakan Village, Situbondo. The implementation method includes field observation, coordination with village officials, socialization of the dangers of plastic waste to the community and students, as well as beach cleanup actions involving students, the community, and elementary school students. The collected waste is then sorted by type to facilitate further management. The results of the activity show an increase in community participation in maintaining environmental cleanliness, the creation of synergy between students and the community, and the growth of collective awareness about the negative impacts of coastal pollution. The discussion emphasized that a participatory approach through cross-element collaboration is able to increase the effectiveness of environmental management programs and support the sustainability of similar activities. In conclusion, the beach clean-up action at the foot of Pecaron Hill not only contributes to improving environmental quality, but also strengthens community concern as social capital in supporting the development of sustainable marine tourism.